2018
DOI: 10.3389/fmicb.2017.02689
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and Stress Responses of Shigella flexneri Regulated by PhoP/PhoQ

Abstract: The two-component signal transduction system PhoP/PhoQ is an important regulator for stress responses and virulence in most Gram-negative bacteria, but characterization of PhoP/PhoQ in Shigella has not been thoroughly investigated. In the present study, we found that deletion of phoPQ (ΔphoPQ) from Shigella flexneri 2a 301 (Sf301) resulted in a significant decline (reduced by more than 15-fold) in invasion of HeLa cells and Caco-2 cells, and less inflammation (− or +) compared to Sf301 (+++) in the guinea pig … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 60 publications
(93 reference statements)
1
33
0
Order By: Relevance
“…Wild-type strain CHS221 (S221) and its heteroresistance-derived S. aureus isolate CHS221-O (S221-O1) were grown and prepared for total RNA extraction with TRIzol reagent (Invitrogen, Carlsbad, CA, United States) as described previously (Zheng et al, 2018). RNA-Seq of the aforementioned parental and heteroresistance-derived isolates was performed as reported previously (Lin et al, 2017). Raw data (raw reads) of fastq format were firstly processed through in-house perl scripts.…”
Section: Methodsmentioning
confidence: 99%
“…Wild-type strain CHS221 (S221) and its heteroresistance-derived S. aureus isolate CHS221-O (S221-O1) were grown and prepared for total RNA extraction with TRIzol reagent (Invitrogen, Carlsbad, CA, United States) as described previously (Zheng et al, 2018). RNA-Seq of the aforementioned parental and heteroresistance-derived isolates was performed as reported previously (Lin et al, 2017). Raw data (raw reads) of fastq format were firstly processed through in-house perl scripts.…”
Section: Methodsmentioning
confidence: 99%
“…2015) and other virulence-associated genes in many enteric pathogens (Groisman 2001; Bijlsma and Groisman 2005; Alteri et al . 2011; Lin et al . 2018).…”
Section: Resultsmentioning
confidence: 99%
“…PhoP-PhoQ is a twocomponent system, comprising the inner membrane sensor PhoQ and the cytoplasmic regulator PhoP. This system regulates lipid A remodelling in K. pneumoniae in vivo and in vitro (Llobet et al 2015) and other virulence-associated genes in many enteric pathogens (Groisman 2001;Bijlsma and Groisman 2005;Alteri et al 2011;Lin et al 2018). Salmonella Typhimurium knockout strains of phoP and phoQ are highly attenuated for virulence in macrophages and a mouse infection (Miller, Kukral and Mekalanos 1989) and this twocomponent system also makes a small contribution to K. pneumoniae virulence during G. mellonella infections (Insua et al 2013).…”
Section: Cell Envelope Proteins and Regulatorsmentioning
confidence: 99%
“…It is well known that planktonic cells produce EPS in response to a variety of environmental signals such as magnesium deficit and subsequently facilitating bacterial attachment [ 9 ]. Optimal expression of the SfpgdA-orf186-virK-msbB2 locus is associated with low Mg 2+ -containing media and is regulated by the PhoP/PhoQ two-regulatory component system [ 10 , 11 ]. In a previous study, we reported that Shigella strains lacking either PhoP or SfPgdA are highly susceptible to lysozyme degradation and are less resistant to killing by polymorphonuclear neutrophils (PMNs) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%